PENINGKATAN MUTU SEKOLAH DASAR MELALUI EDS - Subangun Subangun; Laily Isroin (MUADDIB Jurnal Kependidikan dan Keislaman, 2018)
This study aims to provide an overview of the application of EDS as an effort to improve the quality of primary schools. This research was conducted in Ponorogo District with elementary school research object and elementary school operator in UPTD Jenangan District and UPTD Pulung District. The approach used in this research is descriptive qualitative. Data collection techniques used are (1) interview, (2) observation, and (3) documentation. The data analysis used is a qualitative technique, namely to examine the problem on a case by case basis because the researcher believes that the nature of a problem one will be different from the nature of the other problem.The results showed that school self-evaluation became an alternative for schools to improve school quality. With school self-evaluation, school strengths and weaknesses are known. Furthermore, with the school self-evaluation, will be known position of school accreditation.